2017
DOI: 10.1177/1362168817730665
|View full text |Cite
|
Sign up to set email alerts
|

Preparing special education teacher candidates to teach English language learners with disabilities: How well are we doing?

Abstract: A utilization-focused evaluation (Patton, 2008) was conducted to systematically investigate special education teacher candidates’ preparation to teach English language learners (ELLs) with disabilities. The results were used to (1) determine current effectiveness of departmental programs and (2) guide program improvement efforts. The initial literature review on ELLs with disabilities and teacher preparation guided the development of a four element framework to organize and analyse the data and results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…This study corroborates with other research that demonstrates the importance of teachers' ability to leverage the multiplicity of students' languages into their instruction and assessment (Artiles and Ortiz, 2002;Jozwik et al, 2020;Ortiz et al, 2020). Miranda et al (2019) examined a special education teacher education program that had revised their curriculum to support the education of EBs with disabilities and found the content about EBs to be disjointed and teachers' sense of efficacy in teaching EBs to be lacking. Due to the insufficient guidance for educators, there remains "an urgent need to clarify the professional competencies that should be expected of bilingual special education teachers" (Wang and Woolf, 2015, p. 49).…”
Section: Monolingual English Presumptions In Educational Programming ...supporting
confidence: 87%
“…This study corroborates with other research that demonstrates the importance of teachers' ability to leverage the multiplicity of students' languages into their instruction and assessment (Artiles and Ortiz, 2002;Jozwik et al, 2020;Ortiz et al, 2020). Miranda et al (2019) examined a special education teacher education program that had revised their curriculum to support the education of EBs with disabilities and found the content about EBs to be disjointed and teachers' sense of efficacy in teaching EBs to be lacking. Due to the insufficient guidance for educators, there remains "an urgent need to clarify the professional competencies that should be expected of bilingual special education teachers" (Wang and Woolf, 2015, p. 49).…”
Section: Monolingual English Presumptions In Educational Programming ...supporting
confidence: 87%
“…An estimated 13.8% of the ELL students were diagnosed with learning disabilities (National Center for Education Statistics, U.S. Department of Education, 2018b). These students brought rich cultural and linguistic diversity to schools, but they posed a challenge for teachers who were accountable for students’ academic performance under the reforms (Lucas, Villegas, Freedson-Gonzalez, 2008; Miranda, Wells, & Jenkins, 2017).…”
Section: Identity Reforms and The Education Sectormentioning
confidence: 99%
“…Miranda et al (2019) found that teacher education programs in their study did not adequately prepare their preservice teachers for supporting dually identified students, with EL and special education instructional approaches often taught separately. This fuels the challenges that arise from the “intersectional gap” and interferes with teachers’ abilities to properly support dually identified students.…”
Section: Triads and Transition Planningmentioning
confidence: 86%
“…Furthermore, these low expectations are structurally reinforced through the education system, which perpetuates a deficit orientation toward students who do not fit neatly within the status quo and instills deficit beliefs within individual teachers (Paris, 2012). Miranda et al (2019) found that teacher education programs in their study did not adequately prepare their preservice teachers for supporting dually identified students, with EL and special education instructional approaches often taught separately. This fuels the challenges that arise from the "intersectional gap" and interferes with teachers' abilities to properly support dually identified students.…”
Section: Triads and Transition Planningmentioning
confidence: 99%